TAGES OF DEVELOPMENT OF COTTON BREEDING IN UZBEKISTAN. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
As a result of many years of hard work of our breeding scientists, many high-yielding, disease-resistant, early-early varieties with low technological quality indicators were created, and agricultural crops recommended for planting in the territory of the Republic of Uzbekistan were included in the State Register. and is being planted in large areas of our country.